Carotenoid production by Rhodotorula mucilaginosa in batch and fed-batch fermentation using agroindustrial byproducts - Rodrigues, Tábita Veiga Dias (Array, 2019)
Carotenoids are natural pigments that can be produced through biotechnological processes. However, the costs are relatively high and can be minimized by using lower-cost substrates as alternative nutrient sources. The fed-batch fermentation is one of the techniques used to obtain a high biomass concentration and/or maximum production. Thus, the aim of this work is to produce carotenoids in batch and fed-batch fermentation with the yeast Rhodotorula mucilaginosa CCT 7688 using agroindustrial byproducts in the culture medium. Carotenoid production was increased using experimental designs, which modified the concentration of the agroindustrial medium. In batch production the highest concentrations of total carotenoids (1248.5 μg/L) and biomass (7.9 g/L) were obtained in the medium containing 70 g/L sugar cane molasses and 3.4 g/L corn steep liquor at 25 °C and 180 rpm in 168 h, demonstrating an increase of 17 % when compared to the standard yeast malt medium (1200 μg/L). In the fed-batch production, different feeding strategies were tested with 30 g/L sugar cane molasses and 6.5 g/L corn steep liquor, reaching a total carotenoid production of 3726 μg/L and biomass concentration of 16 g/L. Therefore, the strategy of the fed-batch process resulted in an increase in the carotenoid production of approx. 400 % compared to that in the batch process (740.3 μg/L). Thus, the R. mucilaginosa strain has the potential to produce carotenoids in agroindustrial medium.